Upaya Peningkatan Hasil Belajar Lompat Jauh Dengan Pendekatan Metode Drilling Pada Siswa SD Negeri Biai - Hewilno Simon YF; Ahmad Adil; Imam Suyudi; Irvan Irvan; Muh. Adnan Hudain (Journal on Education, 2024)
This research aims to improve long jump learning outcomes in grade VI at SDN (public elementary school) Biai by using the drilling method. This research is a Classroom Action Research (PTK). The research subjects were 22 students of grade VI at SDN Biai. The data analysis techniques used were observation sheet data analysis and learning result test analysis. The conclusion of this research is that there is an increase in long jump learning outcomes by using the drilling method in grade VI students at SDN BIAI indicated by the increase in the average score of students.